2004
DOI: 10.1111/j.0031-9317.2004.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization ofSEPALLATA3andAGAMOUSorthologues in silver birch

Abstract: The development of flowers is regulated by a complex network of transcriptional activators and repressors, many of which belong to the MADS box gene family. In this study, we describe two MADS box genes of silver birch (Betula pendula Roth), BpMADS1 and BpMADS6, which are similar to SEPALLATA3 and AGAMOUS in Arabidopsis thaliana, respectively. In situ hybridization showed that BpMADS1 was expressed in the inflorescence meristem at a very early stage, but not later. Both genes were expressed in developing carpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…Ermolaeva et al (2003) indicated that SEP1 and SEP2 have recently undergone duplication in the evolution of flowering plants, but their relationships to SEP3 and SEP4 were not clear. Some studies have suggested that SEP1 and SEP2 were more closely related to SEP4 than to SEP3 (Yu and Goh 2000;Lemmetyinen et al 2004;Zahn et al 2005), whereas others suggested that SEP3 was the closest relative of SEP1 and SEP2 (Purugganan 1998;Lawton-Rauh et al 2000;Sung et al 2000;Becker and Theissen 2003;Parenicova et al 2003;Vandenbussche et al 2003b). Our phylogenetic analysis by the NJ method supports the latter hypothesis, showing that SEP3 is more closely related to SEP1 and SEP2 (Fig.…”
Section: Perspectives On the Functional Evolution Of Sep-like Genes Imentioning
confidence: 99%
See 1 more Smart Citation
“…Ermolaeva et al (2003) indicated that SEP1 and SEP2 have recently undergone duplication in the evolution of flowering plants, but their relationships to SEP3 and SEP4 were not clear. Some studies have suggested that SEP1 and SEP2 were more closely related to SEP4 than to SEP3 (Yu and Goh 2000;Lemmetyinen et al 2004;Zahn et al 2005), whereas others suggested that SEP3 was the closest relative of SEP1 and SEP2 (Purugganan 1998;Lawton-Rauh et al 2000;Sung et al 2000;Becker and Theissen 2003;Parenicova et al 2003;Vandenbussche et al 2003b). Our phylogenetic analysis by the NJ method supports the latter hypothesis, showing that SEP3 is more closely related to SEP1 and SEP2 (Fig.…”
Section: Perspectives On the Functional Evolution Of Sep-like Genes Imentioning
confidence: 99%
“…Vandenbussche et al (2003b) reported that FBP2 and FBP5 in petunia were required for B, C, and D floral organ identity functions, based on the analysis of fbp2fbp5 double mutants. Moreover, two MADS-box genes in silver birch (Betula pendula: Betulaceae), BpMADS1 and BpMADS6 (Lemmetyinen et al 2004), and two genes in apple (Malus domestica: Rosaceae), MdMADS3 and MdMADS4 (Sung et al 2000), are phylogenetic and functional homologues to SEP-like genes. These results imply that these sets of genes have similar functions among these plants and perhaps function in more distantly related groups as well.…”
Section: Introductionmentioning
confidence: 99%
“…In woody plants, the functional homology of the AG gene has been identified from a diverse number of species, such as palm (Zhang et al 2004), spruce (Rutledge et al 1998;Tandre et al 1998), hazelnut (Rigola et al 1998), birch (Lemmetyinen et al 2004), grape (Boss et al 2001), poplar (Brunner et al 2000), gingko (Jager et al 2003), rose (Kitahara and Matsumoto 2000), and apple (van der Linden et al 2002). In situ hybridization and ectopic expression has been widely used to assess expression pattern of AG homologs.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that SEP proteins are required for all ABC SEP1 and SEP2 are believed to be the result of a recent gene duplication (Ermolaeva et al 2003) but their relafunctions, along with the possibility that SEP genes are angiosperm specific, suggests that the evolution of SEP tionships to SEP3 and SEP4 are not clear. Some analyses place SEP1 and SEP2 more closely to SEP4 than to SEP3 homologs may be intimately associated with the evolution of the angiosperms and may even be partly responsi-(Yu and Goh 2000; Lemmetyinen et al 2004), whereas other studies concluded that SEP3 is the closest relative ble for the emergence and subsequent explosion of angiosperms. In this article, we have identified SEP hoof SEP1 and SEP2 (Purugganan 1998;Lawton-Rauh et al 2000;Sung et al 2000;Becker and Theissen 2003; mologs from angiosperms that occupy phylogenetically important positions.…”
mentioning
confidence: 99%
“…Their role in floral development is directly demonstrated by SEP subfamily has a potentially conserved meristematic identity or determinacy function (Bonhomme et al 1997, genetic studies in the eudicots Arabidopsis and petunia and strongly supported by expression studies in a num-2000; Yu and Goh 2000; Theissen 2001; Lemmetyinen et al 2004). Although AP1 also has meristem activities ber of other species in both the eudicot and monocot clades.…”
mentioning
confidence: 99%